Phytosociological description of Quercus petraea forest stands with Chamaecytisus hirsutus and Erica carnea in the Vipavska brda (southwestern Slovenia) - Igor Dakskobler (Slovenian Forestry Institute, 2014)
We conducted a phytosociological study of Quercus petraea stands, whose herb layer is dominated by Erica carnea in the flysch hills of Vipavska brda and on the margins of the Vrhe plateau (southwestern Slovenia). We have determined that they are a long-term degradation stage on beech forest sites from the association Seslerio autumnalis-Fagetum. Based on comparisons with similar sessile oak stands from associations Melampyro vulgati-Quercetum petraeae, Seslerio autumnalis-Quercetum petraeae and Erico carneae-Quercetum petraeae, the studied stands are classified into the new association Chamaecytiso hirsuti-Quercetum petraeae. They are best differentiated from the stands of compared communities by the species Erica carnea, Sorbus aria, Lathyrus linifolius, Loranthus europaeus and Erythronium dens-canis. The new association is classified into the alliance Carpinion orientalis and order Quercetalia pubescenti-petraeae.